Efficacy and Safety of Collagenase Clostridium Histolyticum in the Treatment of Peyronie's Disease: An Evidence-Based Analysis - Cao, Dehong; Li, Jinze; Lu, You; Huang, Yin; Chen, Bo; Chen, Zeyu; Shen, Yinzhi; Liu, Liangren; Wei, Qiang (Frontiers in Medicine, 2022)
Background: Peyronie’s disease (PD) is a chronic wound healing disorder, mainly involving tunica albuginea. Collagenase Clostridium Histolyticum (CCH) has shown its effectiveness in treating PD, but its efficacy and safety remains controversial, which propelled us to conduct the first evidence-based research on this topic. Methods: We searched Web of Science, PubMed, Embase, and ClinicalTrials.gov for related randomized controlled trials (RCTs). A systematic review and meta-analysis were performed to compare the penile curvature deformity (PCD), Peyronie's Disease Questionnaire peyronie’s disease symptom bother (PDSB), penile pain score, total treatment-related adverse events (TAEs) and specific adverse events, including penile pain, penile edema, injection site pain and contusion. Cochrane Collaboration’s tool and Review Manager 5.3.0 version were applied respectively to evaluate the study quality and heterogeneity. Results: Four articles (five RCTs) with 1227 patients were finally included for the meta-analysis. The results revealed that CCH had excellent efficacy in relieving PCD (weighted mean difference [WMD]: -318.77, P < 0.001) and PDSB (WMD: -1.20, P < 0.001) compared to the placebo group, but there was no difference in penile pain score (WMD: -0.64, P = 0.39) between the two groups. Furthermore, the incidence of TAEs in the CCH group was higher (odds ratio [OR]: 12.86, P < 0.001). Conclusions: The current evidence suggests that CCH has a significant effect in treating PD. Considering that all these adverse events are acceptable and curable, CCH could slow the disease progression in the acute phase or act as a substitute for patients unable or unwilling to undergo surgery. However, the conclusion could not be drawn certainly until RCTs with larger scale proved it.